Perspectivas y límites de la investigación sociolingüística contemporánea (reflexiones programáticas a propósito del proyecto de investigación del sistema de variedades vernáculas malagueñas) - Villena Ponsoda, Juan Andrés (ELUA: Estudios de Lingüística. Universidad de Alicante, 1988)
Urban dialectology and research into vernacular varieties, sociolects, and related phenomena have been developing in recent years within European sociolinguistics, through a very ineresting combination of American fieldwork methods (Labov et alii) with others developed by social anthropologists and well tested in the area of linguistics (Gumperz, Milroy et alii). The further differences between national trends in European urban vernacular research come from each country's own traditions in linguistic and social studies (functionalism, historical dialectology, educational sociology, marxism, and so forth). The aim of this paper is to carry out a critical revision of the European (and, especially, Spanish) methodological and theoretical foundations of studies of urban sociolinguistics variation and change, inasmuch as the said foundations are considered a framework for the analysis of the Vernacular Varieties System of Málaga (V.U.M.-Project). A brief report of its limits and perspectives is presented, with special emphasis placed on the linguistic and sociolinguistic features of Andalusian Spanish (as far as they are known the unsystematic previous observations). Andalusian varieties of Spanish can be defined, from an outer point of view, as taking part in a polynomic system (Marcellesi); from an inner point of view, the could be classified as a diasystem of gradata (Stehl), with two well defined extremes consisting of highly-focussed varieties (Standard Spanish and Cross-regional and Urban Educated Regional Standards /versus/ Low Varieties of Andalusian Spanish), and an intermediate part where a vast range of variation occurs (diffusion).